大気大循環モデルを用いた南極周辺の海氷が大気循環に与える影響 - 緒方, 香都; 立花, 義裕; 大島, 和裕; Koto, Ogata; Yoshihiro, Tachibana; Kazuhiro, Oshima (2013)
We investigated an influence of sea ice anomaly in the Pacific sector of the Southern Ocean upon large-scale atmospheric circulation using an Atmospheric General Circulation Model (AGCM). It is well known that Pacific South American (PSA) teleconnection pattern is induced by El Niño-Southern Oscillation (ENSO) over the Southern Hemisphere. Changes in zonal winds associated with the PSA pattern affect sea ice anomalies in the Amundsen-Bellingshausen Sea (Pacific sector) and the Weddell Sea (Atlantic sector) of the Southern Ocean, which is called Antarctic Dipole (ADP) pattern. Based on the ADP sea-ice anomalies, an AGCM simulation under the low sea-ice condition in the Pacific sector and Atlantic sector (Ice run) are conducted. Comparison of geopotential height at 500 hPa between the Ice run and NCEP/NCAR Reanalysis indicated that the sea ice condition in the Pacific sector enhances positive phase of PSA pattern anomalies over western part of the Southern Hemisphere. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月14日（木） 統計数理研究所 ３階セミナー室１（D305） conference object